2014
DOI: 10.1038/ncomms6867
|View full text |Cite
|
Sign up to set email alerts
|

COP1 E3 ligase protects HYL1 to retain microRNA biogenesis

Abstract: Constitutive photomorphogenic 1 (COP1) is a RING-finger E3 ligase that plays a central role in photomorphogenesis by destabilizing many light-regulated transcription factors and photoreceptors. Here, we reveal a novel function for COP1 E3 ligase in controlling global miRNA biogenesis in Arabidopsis thaliana. In cop1 mutants, the level of miRNAs is dramatically reduced because of the diminution of HYPONASTIC LEAVES 1 (HYL1), an RNA-binding protein required for precise miRNA processing. HYL1 is destabilized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
122
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 52 publications
8
122
1
Order By: Relevance
“…Further experiments propose that the cytosolic fraction of COP1 which is present in light-grown seedlings protects HYL1 from cleavage by an unknown protease. Consistent with this idea full-length HYL1 levels are higher in light-grown than in dark-grown seedlings [75].…”
Section: A Few Glimpses Into Novel Functions Of Cop1mentioning
confidence: 65%
“…Further experiments propose that the cytosolic fraction of COP1 which is present in light-grown seedlings protects HYL1 from cleavage by an unknown protease. Consistent with this idea full-length HYL1 levels are higher in light-grown than in dark-grown seedlings [75].…”
Section: A Few Glimpses Into Novel Functions Of Cop1mentioning
confidence: 65%
“…In Arabidopsis , the dephosphorylation of HYL1 by CPL1 is required for accurate miRNA processing and strand selection from miRNA duplexes [20]. A well-studied regulator of photomorphogenesis, constitutive photomorphogenic 1 (COP1), was found to affect miRNA accumulation through regulation of HYL1 [52]. In this study, we showed that SnRK2 kinases affect miRNA expression, possibly by modulating key components of the Arabidopsis miRNA processing complex.…”
Section: Discussionmentioning
confidence: 90%
“…2/3/6 triple mutant or mannitol-treated seedlings of the snrk2 decuple mutant is due to increased degradation or decreased protein synthesis of HYL1. Recently, Cho et al also found that the level of HYL1 is highly diminished in a cop1 mutant background and suggested involvement of yet to be identified protease X in the proteolysis of HYL1 [52]. It would be interesting to know if there is a potential biochemical link between SnRK2-mediated HYL1 stabilization and COP1-mediated HYL1 stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HYL1 activity is controlled by phosphorylation and dephosphorylation (30,31). Furthermore, the expression levels of the DCL1 complex are regulated at transcriptional and posttranscriptional levels to influence miRNA accumulation (32)(33)(34). The structure and length of the stem-loop also impact pri-miRNA processing.…”
mentioning
confidence: 99%